A Note on “More For Less” Paradox in Relation to Economic Problems - Miroslav Plevny (Communications - Scientific letters of the University of Zilina, 2003)
The More for Less Paradox is not only an interesting theoretic construction. An optimization problem, which has this interesting property, can also be found in the real economic world. This contribution was stimulated by the paper [4], which results from the contribution [1] and [2] discussing one interesting property of the linear programming models behaviour, and comments on it and discusses it further. In the paper we attempt to show on a concrete case of a real practical problem [5] that similar property does not need to be a purely theoretical plaything, and it can also be spotted when analysing different variants of a real problem solution.